PERENCANAAN NORMALISASI SUNGAI BERINGIN DI KOTA SEMARANG - Putra, Dimaz Pradana; Suharyanto, Suharyanto; Nugroho, Hari (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Reduced green open areas and forests in upstream of Beringin watershed areas is affect the run-off, so it is possible resulting in increased surface run-off, decreased time of concentration, and at the same time a decrease in groundwater recharge. Thus the flow in the rainy season will tend to rise and discharge will decrease in the dry season. Comparison of river's Qmax (usually in the rainy season) and Qmin (in the dry season) is very large. The greater the ratio of river's Qmax to Qmin, indicating the further degradation of the watershed. Upstream areas in the South is quite hilly with steep slopes, with a height of 12.5 m to 250 m. The issue of Beringin River originated from land use change in the uplands, especially on open land (forest, shrubs, and farm or agricultural) into housing and settlement, causing flooding in the watershed Beringin. To calculate the average maximum rainfall-average using Thiessen polygon method with three rainfall stations that affect which is the Mijen, Tugu, and Mangkang Waduk. Rainfall data were used from 2003 till 2012, while the flood discharge plans taken from the calculation method of HSS Gama I with a return period of 10 years at 180.59 m3/s. Normalization is planned in the main river along the 7.18 km, from the estuary (STA 0) to the arround Mangkang regency (STA 23). Varying the width of the river is 14 m of STA 0 to STA 8, 12 m of STA 9 to STA 19, and 10 m of STA 20 to STA 23 with the same slope at 1: 1.5. This cross section plan has previously been simulated with HEC-RAS 3.1.3 program and the results was they were able to accommodate discharge plan that occurs. Safety height of 0.6 m was added in each cross section above the water level of the river. Revetments also added to the bend of the river in STA 22-23 with a length of 200 m and a height of 4m. This project implementation is scheduled for 28 weeks with a budget plan of of Rp 16,881,359,000.00.